The Neuroprotective Effects of GLP-1 Analogues on Alzheimer’s Disease – A Literature Review - Ulicka, Wiktoria; Dudek, Patryk; Łuczak, Klaudia; Marcel Chudzikowski; Pawlik, Agnieszka; Pięta, Justyna; Tabeau, Adrianna; Sitarek, Hanna; Prus, Joanna; Prokopiuk, Agata (Journal of Education, Health and Sport, 2025)
Alzheimer’s disease (AD), often referred to as type 3 diabetes, is characterized by neuroinflammation, oxidative stress, mitochondrial dysfunction, and brain insulin resistance, leading to cognitive decline. GLP-1 receptor agonists, originally developed for type 2 diabetes, demonstrate neuroprotective properties that address these pathologies. They improve insulin sensitivity, reduce amyloid-beta deposition, tau hyperphosphorylation, and neuronal apoptosis while enhancing synaptic plasticity, autophagy, and neural stem cell proliferation. Studies highlight their potential as innovative AD therapies. However, further research is needed to confirm their efficacy and long-term safety in combating neurodegeneration.